(untitled) (Siddhajyoti Interdisciplinary Journal, 2020)
This study employed bounds test based cointegration technique using annual time series data from the period 1990/91 to 2015/16 for exploring relationship between RGDP and FDI in Nepal. This paper examines the effect of FDI on RGDP is insignificant at five percent level of significance. The coefficient (0.35) of (FDI) shows that one percent increase in FDI leads to over 0.35 percent increase RGDP in the long-run. There is no causality between foreign direct investment and economic growth.